Innovations in Military Education as a Condition for Forming Professional Competence (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article deals with innovations in military education, which are understood as new methods of teaching, new ways of organizing classes, formation of the content of education (integration ( intersubject ) programs), methods for assessing the educational result.